Analisis Tingkat Kepuasan Nasabah Pengguna Byond by BSI - Abdul Munir; Marabona Munthe (Journal of Islamic Banking, Economics and Finance, 2025)
This study aims to see how big the level of customer satisfaction in using the Byond by BSI application in Riau province and to find out how big the influence of service quality, product quality, convenience and security on customer satisfaction who use Byond by BSI, and to find out how satisfied customers are in using Byond by BSI. The research method of data analysis uses quantitative using the Multiple Linear Regression approach. The results of the study indicate that customer satisfaction of Byond by BSI users in Riau Province is relatively very satisfied. This can be seen based on the results of the study that the number of high satisfaction responses from respondents' answers, in terms of service quality with a significant value of 0.001 with a positive regression value of 0.183%, product quality with a significant value of 0.001 with a regression value of -0.244% ease of use with a significant value of 0.001 with the highest regression value of 0.458%, and security with a significant value of 0.002 with a regression value of 0.206%.